The short-term effects of recombinant human growth hormone on children with growth hormone deficiency and idiopathic short stature: a retrospective study - Li, Mei; Feng, Jun; Chen, Liqin; Huang, Dongmei; Wu, Xia; Zhang, Zhang; Wang, Wenmin (Acta Biomedica Atenei Parmensis, 2024)
Background: To evaluate the short-term efficacy and safety of recombinant human growth hormone (rhGH) in treating children with growth hormone deficiency (GHD) or idiopathic short stature (ISS). Methods: Records of children diagnosed with GHD or ISS at Yulin Maternal and Child Health Care Hospital of Guangxi from April 2021 to February 2023 were analyzed. Of 90 children, 33 had GHD and 57 had ISS. Results: Post-rhGH treatment, significant elevation in height, weight, bone age and IGF-1 level was observed in both groups at 6 and 12 months. The efficacy was similar for both conditions, except for a distinction in bone age at 6 months. No difference was seen in the effectiveness of rhGH in powder vs. liquid form. Insulin levels increased post-treatment, with no change in liver, kidney, and thyroid parameters for GHD children. However, significant changes were seen in ISS children’s liver, kidney, and thyroid parameters. Adverse reaction rates were comparable between groups. Conclusions: rhGH improved the growth velocity/year in GHD or ISS children. Notably, some changes in the liver, kidney, and thyroid parameters were observed in children with ISS after rhGH treatment. It indicates the importance of monitoring these functional indicators, although the exact magnitude and clinical significance of these changes need further investigation.